Role of Adipose Tissue-Derived Mesenchymal Stromal Cells in Preventing Rejection in Rat Intestinal Transplantation. (July 2018) - Andres, Ane; Hernandez-Oliveros, Francisco F; Santamaria, Monica; Stringa, Pablo; Largo, Carlota; García-Arranz, Mariano; de las Heras, Soledad García; Vallejo, Maria Teresa; Aras, Rosa; Guerra-Pastrian, Laura; Tovar, Juan A; López-Santamaría, Manuel
Abstract : Aim and Background: Standard immunosuppressants to prevent rejection in solid organ transplantation are not exempt from complications. Mesenchymal stromal cells (MSC) have been proposed as a promising alternative, either alone or combined, both for its safety and for its regenerative and immunomodulatory properties. In experimental models of intestinal transplantation, there is only one published article describing their advantages. Interestingly, we found different results in our study using adipose tissue-derived MSCs (Ad-MSC), more easily obtainable and richer in MSCs. Additionally, we compared the efficacy of allogeneic versus autologous Ad-MSCs. Also, we tested the feasibility of the intraarterial route to administer the cells, thus ensuring their arrival to the graft after reperfusion. Methods: An acute rejection rat model after allogeneic intestinal transplantation was developed, using highly histoincompatible strains (Brown Norway as donors and Lewis as recipients). Four experimental groups were established: 1.-Control (n=6), 2.-Tacrolimus 5 days (n=4); 3.-Control + MSCs (n=11); 4.-Tacrolimus 5 days + MSCs (n=11), all of them euthanized in the 14th POD day. One additional group with daily Tacrolimus until euthanasia was used as negative control for rejection (n=6). MSCs were isolated from adipose tissue of Sprague rats (Third-party allogeneic cells) in half of them (n=6 and n=5), and from Lewis rats (Autologous MSCs) in the other half (n=5 and n=6, respectively). 1.5-2 x 10 6 MSCs diluted in 1 ml of Ringer Lactate were injected through the superior mesenteric artery, just before reperfusion. Non parametric tests were used to analyze differences between groups, regarding overall survival, development and severity of rejection, clinical features, immune cell subpopulations in the graft, and plasmatic cytokine expression. Results: No surgical complications appeared after the intraarterial administration of the cells. We found some significant differences in the cell count of different immune cell subpopulations (macrophages CD68+, CD4+, CD8+, CD20+ and Foxp3+) supporting an immunomodulatory role of the Ad-MSCs (p<0.05). We also found differences in the plasmatic cytokine and chemokine secretion, as for those with proinflammatory as with antiinflammatory profile. However, we did not observe differences between the third party and the autologous groups. Neither did we find significant differences in survival or in the degree of rejection in those animals treated with additional MSCs. Conclusion: Despite the findings supporting an immunomodulatory role, it is possible that the MSCs administered just during the transplant did not prevent clinical rejection due to the proinflammatory environment at that moment, redirecting the tolerogenic role of these cells towards one more proinflammatory, able to face the immunological insult of the transplant. This study opens the door to future studies which will probably give us the key to administer the MSCs in the optimal moment, and with the correct dose, administration route, and environmental conditions, to get the expected effect.